'Knowledge is power': A framework for partnering with consumers in developing and delivering a scientific meeting in nephrology. Issue 5 (2nd May 2019) - Duncanson, Emily; Dansie, Kathryn; Gutman, Talia; Tong, Allison; Howell, Martin; Jesudason, Shilpanjali; Reidlinger, Donna; Williamson, Amber; Scholes‐Robertson, Nicole; Murphy, Lisa; Hawley, Carmel M; Craig, Jonathan C; et al.
ABSTRACT: Involving consumers (patients, carers and family members) across all stages of research is gaining momentum in the nephrology community. Scientific meetings present a partnership opportunity with consumers for dissemination of research findings. The Better Evidence and Translation in Chronic Kidney Disease (BEAT‐CKD) research collaboration, in partnership with Kidney Health Australia, convened two consumer sessions at the 54th Australian and New Zealand Society of Nephrology Annual Scientific Meeting held in September 2018. The educational objectives, topics and session formats were informed by members of the Better Evidence and Translation‐Chronic Kidney Disease Consumer Advisory Board (which at the time comprised 36 consumers from around Australia with varied experience of kidney disease). Patients, health professionals and researchers facilitated and presented at the sessions. In‐person and live‐streaming attendance options were available, with over 400 total participants across the two sessions. Sessions were also video recorded for dissemination and later viewing. Evaluations demonstrated consumers found the presentations informative, relevant and accessible. Attendees indicated strong interest in participating in similar sessions at future scientific meetings. We propose a framework for partnering with consumers as organisers, facilitators, speakers and attendees at scientific meetings in nephrology.